Effect of samarium on the physical, structural and optical properties of borotellurite glass system / Siti Nasuha Mohd Rafien - Mohd Rafien, Siti Nasuha (2016)
A series of glasses with composition (70-x)TeO2 + 20B2O3 + 10ZnO + xSm2O3, where 0.0 ≤ x ≤ 2.5 mol % has been prepared with different concentration of samarium ions using melt-quenching method. The amorphous nature of the glass has been investigated through X-Ray Diffraction (XRD) and all glasses are found to be amorphous in nature. The physical, structural and optical properties are determined. The density of glass was found to increase steeply before it suddenly drop while the molar volume was found to decrease before it start to increase with respect to Sm3+ content. FTIR spectroscopy has been used in order to identify the structure of the glass system. From FTIR spectra, the absorption bands are found in the regions around 714- 725 cm-1, 839-855 cm-1, 1215-1218 cm-1, 1362-1367 cm-1, 2993-3003 cm-1 and 3741-3748 cm-1 which correspond to the stretching vibration modes. The absorption spectra displayed three strong absorption peaks corresponding to the 6H5/2 → 4L13/2, 6H5/2 → 4M19/2 and 6H5/2 → 4I11/2 transitions respectively which located at 403 nm, 422 nm and 480 nm. Meanwhile, the emission spectra of Sm3+ doped borotellurite glass which correspond to the 4G5/2 → 6H5/2, 4G5/2 → 6H7/2, 4G5/2 → 6H9/2 and 4G5/2 → 6H11/2 transitions at 562 nm, 599 nm, 645 nm and 706 nm respectively were observed under the 480 nm excitation wavelength. The photoluminescence result reveal that 1.0 mol% of Sm3+ ions is found to be the optimum concentration as it shows the most intense emission spectra.